2014
DOI: 10.1007/s00586-014-3458-9
|View full text |Cite
|
Sign up to set email alerts
|

Surgical strategies for removal of intra- and extraforaminal dumbbell-shaped schwannomas in the subaxial cervical spine

Abstract: Total removal of intra- and extraforaminal cervical subaxial schwannomas could be possible using a posterior approach with facet removal if the size of extraforaminal tumor was less than 5.4 mm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…The incidence of dumbbell tumors is 13.71–17.5% in spinal cord tumors [3, 4]. The rate of dumbbell tumors in the cervical spine was significantly higher than that of other spinal segments [5].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of dumbbell tumors is 13.71–17.5% in spinal cord tumors [3, 4]. The rate of dumbbell tumors in the cervical spine was significantly higher than that of other spinal segments [5].…”
Section: Introductionmentioning
confidence: 99%
“…The preferred method may be tumor resection with laminectomy, with or without posterior stabilization. [7]. In the presented case, posterior stabilization was not preferred; instead, 3-level laminoplasty was performed, and there was no severe kyphosis on control X-ray at the end of the third postoperative month.…”
Section: Discussionmentioning
confidence: 77%
“…Additionally, another limitation of this study is the lack of quantitative analyses of preoperative and postoperative tumor size. Previous studies measured tumor size as the longest diameter of the tumor on axial MRI [ 7 , 11 , 14 , 21 ] and reported that preoperative and postoperative tumor sizes were not significant risk factors for remnant tumor growth [ 7 , 14 ]. However, discrepancies between measurements of tumor size only on axial MRI and the actual 3-dimensional tumor size were much concerned.…”
Section: Discussionmentioning
confidence: 99%
“…size as the longest diameter of the tumor on axial MRI 7,11,14,21 and reported that preoperative and postoperative tumor sizes were not significant risk factors for remnant tumor growth. 7,14 However, discrepancies between measurements of tumor size only on axial MRI and the actual three-dimensional tumor size were much concerned.…”
Section: A C C E P T E D a R T I C L Ementioning
confidence: 99%